Kajian Literatur Analisis Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Peningkatan Hasil Belajar Peserta Didik Sekolah Dasar - Ari Suriani; Ella Resma Nofica (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2025)
This article focuses on assessing how well the Jigsaw method of cooperative learning enhances educational achievements among elementary school students, based on several prior studies. The research involved a review of literature that included seven investigations related to the use of the Jigsaw method in subjects such as science, social studies, mathematics, civics, and the Indonesian language at the elementary level. The findings indicated that implementing this model can reliably boost the average score, completion rates, retention of information, and student engagement during lessons. Furthermore, the Jigsaw approach fosters teamwork among students and encourages them to share their thoughts confidently. Therefore, it can be concluded that the Jigsaw cooperative learning method is effective in enhancing student academic performance and is advisable as a strategy for active learning in classrooms.